Konflik Antar Negara Berdasarkan Hukum Internasional - Vera Yanti Artega; Adwani Adwani; Sanusi Bintang (Kanun Jurnal Ilmu Hukum, 2019)
Penelitian ini bertujuan untuk menjelaskan perlindungan hukum internasional terhadap negara yang disadap secara melawan hukum oleh negara lain dan menjelaskan metode penyelesaian sengketa yang dilakukan Indonesia dalam  menyelesaikan konflik antar negara akibat penyadapan yang dilakukan Australia terhadap Indonesia Tahun 2013. Penelitian ini menggunakan jenis metode penelitian hukum yuridis normatif. Hasil penelitian menunjukkan bahwa hukum internasional belum memberikan perlindungan yang cukup kepada negara yang disadap oleh negara lain. Adapun metode penyelesaian sengketa yang digunakan Indonesia dalam menyelesaikan kasus penyadapan dengan Australia adalah penyelesaian sengketa internasional secara damai melalui cara negosiasi. Oleh karena itu, peraturan mengenai penyadapan lintas negara harus segera dibentuk, sehingga perlindungan hukum terhadap negara yang disadap bisa dilakukan. Serta kedua negara harus membentuk code of conduct. Inter-State Conflict Under International Law International relation between two countries at some time could evoke problems which are caused by the cheating action of one party, such as interception resulting in conflict between them. This study aims to explain the protection of international law against countries that are illegally intercepted by other countries and explain the method of dispute settlement conducted by Indonesia in resolving inter-state conflicts resulting from Australian interception to Indonesia in 2013. This study uses a normative-juridical legal research method, by using legislation, case study , and conceptual approach with library data sources. The result shows that international law has not provided sufficient protection to countries intercepted or tapped by other countries. The method of dispute resolution used by Indonesia in solving wiretapping case with Australia is the peaceful settlement of international disputes through negotiation. Therefore, regulations concerning cross-country intercepting must be established immediately, thus legal protection of the tapped countries could be proceeded, and the two countries must establish a code of conduct.